(untitled) (Archive of Conferences, 2022)
it would not be an exaggeration to say that a mature scientist and educator in his time , Abdulla Avlani, brought many changes and updates to the education and science sector and the course process through his new intensive actions, pedagogical views. On the basis of his pedagogical views, he finds his solution to the issues of interactivity, activity, mutual respect and upbringing among students of schools and higher educational institutions. In a number of pedagogical works written by Abdulla Avlani, he also gives serious confidence to the principles of upbringing and morality and the sphere of Education. In the course of this article, we will study the pedagogical views of Abdulla Avlani as well as the issue of upbringing in his works